An Investigation of Finite Element Analysis (FEA) on Piezoelectric Compliance in Ultrasonic Vibration Assisted Milling (UVAM) for Preparing Surface Edge Treatment on Cutting Tool - Ibrahim, Rasidi; Rachmat, Haris; Dida, Damayanti; Radzi, Anis; Mulyana, Tatang (Advanced Aspects of Engineering Research Vol. 4, 2021)
Finite element analysis for piezoelectric actuator has been developed in Ansys Software which are a program that can analyses and simulate the dynamic behaviour of piezoelectric. Ultrasonic Vibration assisted Milling (UVAM) process consist a combination of milling operation and vibration system on the compliance mechanism. The Ultrasonic Vibration assisted Milling (UVAM) experimental having a difficulty to investigate the effect of vibration mechanism where existence of error in material, mechanism and attachment of piezoelectric thus affect the amplitude and frequency of mechanical compliance during the machining of UVAM. This paper will investigate the modelling of piezoelectric compliance and follow the procedures of FEA to accurately predict the dynamic behaviour of compliance. The parameters for simulation of piezoelectric are voltage, electromechanical coupling and frequency. The compliance mechanism is model by using Solid Works 2014 and imported to Ansys Mechanical APDL Software were the piezoelectric are embedded on the mechanism. Modal analysis and harmonic analysis has been used in order to obtain the mode shape and displacement. The displacement of the compliance mechanism will be compare between simulation and experimental. The dynamic behaviour was discussed in simulation to study the reliability of the compliance mechanism before it safely used in UVAM. The displacement is important for compliance mechanism because it will affect the accuracy of the vibration of the work piece during machining. Natural frequency mode shape is a modal parameter that we can analyse and prevent the vibration problem causes by resonance.